Can we shorten the q-space imaging to make it clinically feasible? - Sakai, Koji; Yamada, Kei; Akazawa, Kentaro; Tazoe, Jun; Yasuike, Masashi; Nagano, Hitomi; Ikeno, Hiroyasu; Nakagawa, Toshiaki (Japanese Journal of Radiology, 2017)
Purpose: Q-space imaging (QSI) is a novel magnetic resonance imaging (MRI) technique that enables assessment of micro-structural changes of white matter. The acquisition time, however, is comparatively long to use for routine clinical assessment. Therefore, the present study investigated the clinically feasible b value combinations to measure the water molecular displacement probability density function (PDF) in healthy subjects.Methods: The subjects consisted of five healthy volunteers (1 female and 4 male; 40.8 ± 13.2 years). All MRIs were examined at 1.5 T. The QSI was acquired using a single-shot echo-planar imaging and Δ/δ = 142/17 ms. The magnitude of the gradients was incremented in nine steps to reach a maximal b = 10,000 s/mm2. The total acquisition time of this original QSI was 17.4 min. The feasibility of ten alternative b value combinations with the zero-filling or curve fitting technique was assessed. The mean diffusivities (MDs), kurtosis, and zero displacement probability (ZDP) were obtained, and these results were compared in manually segmented regions of interest.Results: There were alternative b value combinations with a 7.5-min acquisition time and with almost the same PDF.Conclusion: A few alternative b value combinations with the curve fitting technique were found to be able to shorten the QSI acquisition for its clinical feasibility of MD and ZDP.